THE ROLE OF GRAMINAE ROOT FUNGAL ENDOPHYTE IN GROWTH AND YIELD IMPROVEMENT OF UPLAND RICE (Oryza sativa L.) - Kandar, Mamat
The restoration of rice field soil health and fertility can be done through the use of biofertilizer input that is adaptive to rice field ecosystem. This approach is in accordance with Low External Input Sustainable Agriculture (LEISA) which supports the concept of integrated and sustainable farming. The technique is a perfectly applicable compare to other system because it is based on national biological resources and is environment friendly. It is hence the right time to develop the usage of microorganism, such as fungal endophyte for agricultural cultivation. The general objective of this study is to examine the role of endophytic fungi derived from several roots of gramineae (grass) plants in increasing the growth and yield of upland rice. While the specific objectives to be achieved are: 1. To obtain and to indentify endophytic fungi from gramineae plant root. 2. Evaluating the endophytic fungi which has the potential to increase the growth of upland rice in vitro. 3. Assessing several metabolites and the phytohormone content of endophytic fungi, which relatded to plant growth promotion. 4. Evaluating the respond of upland rice plant performance after inoculation with endophytic fungi in pot trial. The research was conducted in three stages, namely: stage 1 Conducting Isolation, selection (screening), identification of endophytic fungi from several gramineae roots in West Java (Majalengka and Sumedang Regencies) based on morphology and moleculer data. Stage 2 Selecting the endophytic fungi based on antagonistic respon toward plant pathogenic fungi, identifying metabolic compounds by GCMS method and phytohormone analysis from selected endophytic fungi isolates by HPLC method. Stage 3 Evaluating the response of upland rice plants inoculated with endophytic fungi on growth and yield with observation parameters: root colonization rate, number of productive tillers per clump, root dry weight per plant, stover dry weight per clump, grain content per clump, Harvest index and the weight of 100 grains of grain per clump. Result of stage I, the result from fungal endophyte exploration from graminiae roots (rice, sugarcane, cyperus, reed, elephant grass, and maize) generated 12 isolates acted as plant growth promoting agent. The twelve fungal endophytes identified morphologically and molecularly are Gaeumannomyces graminicola, Meyerozyma guilliermondii, Bipolaris yamadae, Hipocrea virens, Fusarium oxysporum, Fusarium sp, Gaeumannomyces sp, Trichoderma sp, Dothideomycetes sp, Pestaliopsis microspora, Phialemoniopsis curvata and Phialemoniopsis cornearis. The twelve isolates were tested in vitro on rice seedlings by observing plant height, root length, and root infection level as parameters. From experiments, it is showed that fungal endophyte inoculated to rice seedlings affected the average rice plant height, average root length, and average level of root colonization . The best fungal endophyte to accelerate rice plant growth is isolate 11 (I-11) which belongs to species Phialemoniopsis curvata. Based on molecular identification, the ITS DNA sequence is almost 97% similar to database. This fungal endophyte shows white-brownish color colony, soft fluffy edges, and in microscopic observation the conidiophores are ovoid, transparent with septate hyphae. Results of stage II, the results of antagonistic tests with dual culture tests showed a different result of P. curvata endophytic fungi in inhibiting Aspergillus niger and Fusarium moniliformis on the 4th day. Whereas on the 6th day to the 7th day, it has a low inhibitory power against A. niger and F. moniliformis. Therefore the inhibitory zone is not obvious, meaning that the endophytic fungus is not optimal in producing secondary metabolites in the form of antifungal compounds. Some metabolites from GCMS analysis of P. curvata included phenol, lauric acid, phosphonic acid, ethyl-2,4-dihydroksidimetil-5,6-dimetilbenzoat and benzhotiazolesphenol compounds. These metabolites based on several research results have been known to have the potential to inhibit the pathogenic fungi in rice plants. This study also proved that isolate 11 (P. curvata) produced the hormone IAA, Gibberelin and Zeatin Results of stage III, upland rice host plants gave the best response to the treatment that inoculated with a dose of 30 ml of plant-1 (+ 23,4 x 107 konidia ml- 1) to the parameters (1) average root colonization rate, (2) number of productive tillers per clump, (3) plant root dry weight, (4) plant-based dry weight, (5) number of filled grain per clump (5) harvest index and (6) weight of 100 grains of filled grain. Overall from the results of this study it can be concluded that endophytic fungi derived from the roots of gramineae affect the growth and yield of upland rice involving several secondary metabolite chemical compounds and phytohormones.